2006
DOI: 10.1038/sj.emboj.7601478
|View full text |Cite
|
Sign up to set email alerts
|

The human synMuv-like protein LIN-9 is required for transcription of G2/M genes and for entry into mitosis

Abstract: Regulated gene expression is critical for the proper timing of cell cycle transitions. Here we report that human LIN-9 has an important function in transcriptional regulation of G2/M genes. Depletion of LIN-9 by RNAi in human fibroblasts strongly impairs proliferation and delays progression from G2 to M. We identify a cluster of G2/M genes as direct targets of LIN-9. Activation of these genes is linked to an association between LIN-9 and B-MYB. Chromatin immunoprecipitation assays revealed binding of both LIN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
164
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(173 citation statements)
references
References 43 publications
(60 reference statements)
9
164
0
Order By: Relevance
“…Significantly, the expression of genes regulated at the other cell-cycle stages was not diminished; Cyclin E2 that is required for G 1 /S transition was upregulated whereas B-Myb whose expression peaks during S-phase was unaffected (Figure 2b). Interestingly, Cyclin A2 and Cdc2 expression was not significantly changed by depletion of Lin-9 in F9 cells, although previous studies in adult cells showed transcriptional dependence on Lin-9 (Osterloh et al, 2006). B-Myb has been found to be required to remove a repressive E2F4 complex at the Cdc2 promoter (Zhu et al, 2004), and possibly the lack of this repressor in F9 cells makes this activity redundant.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Significantly, the expression of genes regulated at the other cell-cycle stages was not diminished; Cyclin E2 that is required for G 1 /S transition was upregulated whereas B-Myb whose expression peaks during S-phase was unaffected (Figure 2b). Interestingly, Cyclin A2 and Cdc2 expression was not significantly changed by depletion of Lin-9 in F9 cells, although previous studies in adult cells showed transcriptional dependence on Lin-9 (Osterloh et al, 2006). B-Myb has been found to be required to remove a repressive E2F4 complex at the Cdc2 promoter (Zhu et al, 2004), and possibly the lack of this repressor in F9 cells makes this activity redundant.…”
Section: Resultsmentioning
confidence: 84%
“…Specific enrichment was calculated relative to input chromatin levels using % of input ¼ 2 DCt , where DCt ¼ Ct 1% input -Ct IP . Re-ChIP experiments were performed as described by Osterloh et al (2006). Each ChIP experiment was carried out on biological triplicates.…”
Section: Luciferase Reporter Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The DREAM (or LINC) complex is a master regulator of mitotic gene expression during the cell cycle (Schmit et al, 2007, reviewed in Blais and Dynlacht, 2007;Litovchick et al, 2007;Osterloh et al, 2007;Pilkinton et al, 2007a;Knight et al, 2009). Several proteins that are involved in chromosome segregation and cytokinesis, such as Bub1 and survivin, are direct targets of DREAM (Osterloh et al, 2007;Schmit et al, 2007;Pilkinton et al, 2007b;Knight et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several proteins that are involved in chromosome segregation and cytokinesis, such as Bub1 and survivin, are direct targets of DREAM (Osterloh et al, 2007;Schmit et al, 2007;Pilkinton et al, 2007b;Knight et al, 2009). DREAM consists of a fiveprotein core module and associated proteins (Litovchick et al, 2007;Schmit et al, 2007;Pilkinton et al, 2007a;Knight et al, 2009).…”
Section: Introductionmentioning
confidence: 99%